Personal Branding in Online Platform - Shaker, Fahim; Hafiz, Reaz (Global Disclosure of Economics and Business, 2014)
Online personal branding connotes a way to communicate favorable attributes of an individual self in the online platform in order to differentiate oneself from others that will assist to attain the professional goals along with relational aspirations. Numerous studies focused on the importance of having a strong personal brand but mostly ignored the way of developing it in the virtual world.  The objective of the paper is to explore various literatures from different disciplines to address the issue of developing a contextual framework of “construction of online personal brands.” The study covers the area of personality dimensions, personal brand identity both core and extended, influence of surroundings in identity creation in the online environment, individual’s image positioning and management etc.JEL Classification Code: M31; M37